PENGARUH EFKASI DIRI, PENGAMBILAN RISIKO DAN INOVASI TERHADAP NIAT BERWIRAUSAHA MAHASISWA FEB UNIVERSITAS UDAYANA - Wibowo, Akbar Cahyo; Suasana, I Gusti Agung Ketut Gede (E-Jurnal Manajemen, 2017)
This aims of this study for explain the effect of self efficacy, risk taking and innovation on the entrepreneurship intent of D III and S 1 regular students of Faculty of Economics and Business Udayana University class of 2014. This research was conducted at the Faculty of Economics and Business Udayana University. This research used were 156 respondents with non probability sampling technique, especially purposive sampling. The data that have been collected is processed by using multiple regression analysis technique. The results showed that the three independent variables (self efficacy, risk taking, and innovation) had a significant effect on student entrepreneurship intentions. Based on the results of the research, the Faculty of Economics and Business as an educational institution can provide more practical sciences, entrepreneurial seminars so the students can grow their entrepreneurship intention in him. The results of this study can also provide references for students of D III and S 1 regular programs in order to choose to become an entrepreneur and to start create their own job field.